KEPENARIAN SRI WARDOYO DALAM TARI GAMBIRANOM - Prastiyo, Aris (Institut Seni Indonesia Surakarta, 2024)
The Gambiranom dance is a dance with a fanciful theme depicting King Gambiranom or better known as Bambang Irawan. Being in love with Dewi Titisari, this dance was danced by Sri Wardoyo to determine his bachelor's degree at the STSI Surakarta pavilion in 1990.This research uses the theoretical basis of form proposed by Suzane K. Langer, and as an analytical model to describe the Gambiranom dance, using Janet Adshead's interrelated theory, namely dancers, movement, music, accompaniment, make-up and clothing. This research uses descriptive analysis, namely studying the factual history of Sri Wardoyo's life from childhood to adulthood. By explaining the developments and interviews that support most of the research obtained from interview and observation data, the results of data collection are then selected and clarified in accordance with the objectives and formulation of the problem in this writing. After that the results are analyzed and concluded. From the results of this research, it can be obtained that the description is related to Sri Wardoyo's dancing in the Gambiranom dance. Having total will becomes important, with motivation growing strong within a person, this is the main capital in living the world until one's life stops beating. The motivation that was awakened in Sri Wardoyo is clear evidence of the formation of Sri Wardoyo's good dancing skills.